Research progress of bile biomarkers and their immunoregulatory role in biliary tract cancers - Li, Yun-cheng; Li, Kang-shuai; Liu, Zeng-li; Tang, Yong-chang; Hu, Xiao-Qiang; Li, Xing-yong; Shi, An-da; Zhao, Li-ming; Shu, Li-Zhuang; Lian, Shuo; Yan, Zhang-di; Huang, Shao-hui; et al. (Frontiers in Immunology, 2022)
Biliary tract cancers (BTCs), including cholangiocarcinoma and gallbladder carcinoma, originate from the biliary epithelium and have a poor prognosis. Surgery is the only choice for cure in the early stage of disease. However, most patients are diagnosed in the advanced stage and lose the chance for surgery. Early diagnosis could significantly improve the prognosis of patients. Bile has complex components and is in direct contact with biliary tract tumors. Bile components are closely related to the occurrence and development of biliary tract tumors and may be applied as biomarkers for BTCs. Meanwhile, arising evidence has confirmed the immunoregulatory role of bile components. In this review, we aim to summarize and discuss the relationship between bile components and biliary tract cancers and their ability as biomarkers for BTCs, highlighting the role of bile components in regulating immune response, and their promising application prospects.